Efficacy of angiotensin receptor neprilysin inhibitor for maintenance hemodialysis patients with different types of left ventricular ejection fraction heart failure - Jin-cong Li; Nan-hui Zhang; Lei Wang; Jun-meng Peng; Hui-hui Wang; Wen-hui Chen (Linchuang shenzangbing zazhi)
Objective To explore the therapeutic efficacy of sacubitril/valsartan （S/V）, a representative drug of angiotensin receptor enkephalinase inhibitors （ARNI）, in patients with different types of left ventricular ejection fraction （LVEF） heart failure （HF） on maintenance hemodialysis （MHD）. Methods From June 1, 2022 to May 31, 2023, 155 MHD patients with concurrent HF continuously taking S/V for more than 3 months were selected. According to the level of LVEF, they were assigned into three groups of HF with reduced ejection fraction（HFrEF, n=41）, HF with mid-range ejection fraction（HFmrEF, n=42） and HF with preserved ejection fraction（HFmrEF, n=2）. Heart rate （HR）, blood pressure （BP）, hemoglobin （Hb）, Potassium （K+）, uric acid （UA）, estimated glomerular filtration rate （eGFR）, creatinine （Cr）, brain natriuretic peptide （BNP） and echocardiographic findings before and after dosing were retrospectively reviewed. Results After drug dosing, overall population HR [78.0（71.0, 89.0） beats/min vs 82.0（73.0, 95.0） beats/min], systolic blood pressure[138.0（123.0, 158.0） mmHg vs 155.0（139.0, 173.0） mmHg（1 mmHg=0.133 kPa）], diastolic blood pressure[78.0（68.0, 90.0） mmHg vs 90.0（76.0, 100.0） mmHg], BNP level[729.6（234.9, 1942.2） pg/ml vs 2562.7（928.9, 4957.1） pg/ml] and interventricular septal thickness[12.0（11.0, 13.0）mm vs 13.0（12.0, 14.0） mm] were lower than those pre-treatment（all P＜0.05）; LVEF was higher than pre-dosing [58.0（51.0. 61.0）% vs 49.0（40.0, 56.0）%]（P＜0.05）. The difference in proportional distribution of New York Heart Association （NYHA） cardiac function class before and after drug administration was statistically significant（P＜0.05）. In HFrEF group, heart rate[81.0（70.0, 100.0） beats/min vs 94.0（75.5, 110.0） beats/min], systolic blood pressure [130.0（118.0, 152.0）mmHg vs 146.0（128.0, 166.0） mmHg], diastolic blood pressure [80.0（63.5, 89.0）mmHg vs 79.0（72.0, 96.0）mmHg], BNP[1366.9（612.0, 2991.4） pg/ml vs 4294.9（2562.3, 5000.0） pg/ml] and ventricular septal thickness[12.0（11.0, 13.0）mm vs 13.0（11.0, 11.0, 14.0） mm] lower than pre-dosing （all P＜0.05）; LVEF was higher post-dosing than pre-dosing[48.0（42.5, 55.0）% vs 36.0（32.0, 39.0）%]（P＜0.05）. HFmrEF group had a higher post-dosing HR[75.0（68.8, 80.3）beats/min vs 80.5（75.0, 95.0）beats/min], systolic blood pressure[138.0（121.8, 159.0）mmHg vs 158.0（139.0, 181.3）mmHg], diastolic blood pressure[78.0（67.0, 91.3）mmHg vs 92.0（79.8, 104.8）mmHg], BNP[765.5（245.1, 2323.2）pg/ml vs 3179.7（1325.2, 4967.8）pg/ml] and interventricular septal thickness[12.0（11.0, 13.0）mm vs 13.0（12.0, 14.0）mm] declined as compared with pre-dosing （all P＜0.05）; LVEF was significantly higher after dosing[54.5（50.8, 60.0）% vs 47.0（44.0, 48.0）%]（P＜0.05）. In HFpEF group, systolic blood pressure[139.0（129.3, 161.0）mmHg vs 161.5（146.3, 173.8）mmHg], diastolic blood pressure[77.0（70.0, 91.0）mmHg vs 90.5（78.0, 99.8）mmHg], BNP[433.5（171.4, 1237.8）pg/ml vs 1109.0（651.9, 2772.5）pg/ml] and thickness of interventricular septum[12.0（11.0, 12.0）mm vs 13.0（12.0, 14.0）mm] were lower than pre-dosing （all P＜0.05）. LVEF rose obviously post-dosing [60.0（59.0, 65.0）% vs 56.0（54.0, 60.0）%]（P＜0.05）. The differences in K+, eGFR and UA levels before and after dosing were not statistically significant among HFrEF, HFmrEF and HFpEF groups （P＞0.05）. Conclusion S/V has been shown to lower HR, lower BR, improve HF, lessen septal hypertrophy and enhance myocardial contractility in MHD patients with different types of LVEF HF.